Bartonella Infection in Immunocompromised Hosts: Immunology of Vascular Infection and Vasoproliferation. (17th November 2011) - Mosepele, Mosepele; Mazo, Dana; Cohn, Jennifer
Abstract : Most infections by genus Bartonella in immunocompromised patients are caused by B. henselae and B. quintana . Unlike immunocompetent hosts who usually develop milder diseases such as cat scratch disease and trench fever, immunocompromised patients, including those living with HIV/AIDS and posttransplant patients, are more likely to develop different and severe life-threatening disease. This paper will discuss Bartonella's manifestations in immunosuppressed patients and will examine Bartonella's interaction with the immune system including its mechanisms of establishing infection and immune escape. Gaps in current understanding of the immunology of Bartonella infection in immunocompromised hosts will be highlighted.